Stochastic methods for estimation and problem-solving in engineering - Kadry, Seifedine 1977- (IGI Global, Disseminator of Knowledge, 2018)
"This book explores stochastic methods and their applications. It examines current and future works, discuss proposed methods and solutions, and describe challenges and opportunities in this area. It explores the following issues as well: stochastic methods in different kind of engineering and stochastic methods in business and sciences"...
Keywords: Engineering -- Statistical methods; Estimation theory; Industrial engineering -- Mathematics; Aufsatzsammlung